Aplikasi Pupuk Branglai (Brangkasan Kedelai) dalam Upaya Peningkatan Pertumbuhan dan Produksi Beberapa Varietas Tanaman Kedelai (Glycine max L.) - Girsang, Rosmaria; Br.Sitepu, Sri Mahareni; Sagita, Sayang (UNIVERSITAS LABUHANBATU, 2024)
Soybean (Glycine max L.), which is widely grown in Indonesia, is a popular food crop because of its high protein content. This plant plays an important role in increasing protein intake for the community, because it is a safe and economically affordable source of vegetable protein. To increase the productivity of soybean plants, it is not only important to choose quality seed varieties, but also to implement appropriate cultivation practices. One of the main techniques is to use superior seed varieties. Apart from that, increasing the quality and yield of soybean production can be achieved by providing fertilizer that meets the nutritional needs of plants. This research used a Randomized Block Design (RAK) with 2 factors and 2 replications to obtain 24 research plots. Factor I of Branglai Fertilizer (B) which consists of 4 levels,namely: B0=0ml/liter.air/plant, B1=20ml/liter.air /polybag, B2=40 ml/liter.air/polybag, B3 = 60 ml/ liter. water/polybag. Factor II Soybean Variety (V) which consists of 3 levels, namely: V1 = Dega 1 Variety, V2 = Ring 1 Variety, V3 = Devon 1 Variety. The research procedure consists of making fertilizer, land preparation, filling polybags, planting, fertilizer application branglai (soybean stover), determination of sample plants, maintenance and harvest. Keywords: soybean, branglai fertilizer, soybean variety